Ultrasonographic study on follicular dynamics in repeat breeding Holstein Friesian cows - Patel, J A; Kavani, F S; Dhami, A J (The Indian Journal of Animal Sciences, 2011)
Trans-rectal ultrasound scanning ofovaries ofrepeat breeding cows (6) performed daily over one full cycle revealed the presence of2 patterns of ovarian follicular development per cycle, viz. 2-wave (66.66%, n=4) or 3-wave (33.33%, n=2). In two-wave cycle, the first and second waves began at day O.75±0.25 and 13.75±0.48 respectively. In 3-wave cycle, the first, second and third waves began at day 0.50±O.50, 9.00±O.OO and 16.50±O.50 respectively. There was no significant difference between 2-and 3-wave cycles with regard to the day of the emergence of the first wave. The second wave appeared significantly earlier in the oestrous cycle with 3-wave than with 2-wave. The persistence of the first dominant follicle was longer in 2-wave cycle than that in 3-wave cycle. The duration of the growth and static phases and regression phase of the first dominant follicle did not differ between 2- and 3-wave cycles. The maximum diameters of both first dominant follicle and ovulatory follicle were identical in 2- and 3-wave cycles. In 2-wave cycle, the maximum diameter of ovulatory follicle was significantly larger than the first dominant follicle. However, no statistical differences were observed between the maximum diameters of dominant follicles for 3-wave cycles. The 2and 3-wave cycles also differed significantly with respect to the Olean length of intervals between 2 oestruses and between 2 ovulations. The linear growth rate (rom/day) was lower in ovulatory follicle than that in first dominant follicle in 2-wave and 3-wave cycles. The linear growth of ovulatory follicle differed between 2- and 3-wave cycles. In 2-wave cycle, there was no relationship between the development of dominant follicle and presence of CL in either of the ovaries. While in 3-wave cycle, first dominant follicle and ovulatory follicle developed on ovary opposite ofCL. No statistical difference was found in the mean number offollicles recruited per wave in 2- and 3-wave cycles. However, the first wave had a larger number of follicles than subsequent waves. There was a positive correlation between CL diameter and P4 value. The mean plasma P4 values on various days of cycle were higher in 3-wave as compared to 2wave cycle.